The Moral and Ethical Aims of the School Viewed through a Cosmopolitan Prism. Issue 13 (December 2013) - Hansen, David T.
In this chapter, the author proposes to imagine the aims of the school in light of a cosmopolitan philosophy of education. The first section that follows provides a summary account of what the author takes cosmopolitanism to mean. The second section frames a philosophy of education that stems from this account. The third and penultimate section sketches a conception of the school and its moral and ethical aims in light of this philosophy of education. The discussion will foreground normative ideals. Such ideals can be dangerous if they blind people to realities. They can be disappointing if failure to attain them weighs down hard on people. But if ideals are understood as sources of direction rather than as destinations, they can assist educators to sustain their course in the face of obstacles. The author's core purpose here is to highlight why a cosmopolitan orientation can inspire, encourage, and help guide educators in realizing schools for our time.